Impact of vitamin D and vitamin D receptor activator in diabetic nephropathy - Emini Sadiku, Merita (Frontiers in Clinical Diabetes and Healthcare, 2025)
Vitamin D is a hormone which is involved in many physiological processes in addition to bone metabolism and the muscular system. Based on several animal and human studies, it has been established that vitamin D plays an important role in the development of diabetic nephropathy (DN). DN is a frequent and severe chronic microvascular complication of diabetes mellitus (DM). As such, DN and cardiovascular complications are considered the main risk factors for the death of patients with DM. Recent studies have shown the renoprotective effect of VD and its receptor activators (VDRAs or VD analogs based on its effect on endothelial function, preservation of podocytes, anti-inflammatory effect, and direct influence on the renin-angiotensin aldosterone system. The renoprotective effect of VD has been shown to potentially delay the onset of DN, which is the main cause of end stage renal diseases (ESRD). The impact of vitamin D on the recovery of already existing kidney damage is debatable and doubtful. Increasing evidence has shown that the VD/VDR interaction possesses a series of renoprotective effects in DN patients based on the anti-proteinuric, anti-fibrotic, and anti-inflammatory effect, as well as the preventive effect of podocyte damage. Based on this important renoprotective effect, important data for therapeutic and effective methods for DN have also been presented. It was performed a structured search of published research literature for several databases regarding the impact of VD on the pathophysiology of DN as well as its therapeutic implications in terms of renoprotection of VD and VDRA in animal research and human clinical research as RCT, observational studies, systematic reviews and meta-analyses over the last decade.